ANALISIS STRATEGI GURU KELAS DALAM MENGHADAPI SISWA SLOW LEARNER DI KELAS V SDN KELEYAN 2 - Hardiana Hardiana; Alvina Hidayati; Mid’hat Hidayat; Echa Rany Rafika Sari; Novatul Hasanah; Nova Estu Harsiwi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This study was motivated by the presence of slow learner students in elementary schools who experience difficulties in achieving learning competencies, particularly in literacy and numeracy skills. This condition requires the implementation of learning strategies that are tailored to students’ characteristics and needs to optimize the learning process. The purpose of this study was to describe the learning strategies employed by classroom teachers in teaching slow learner students in Grade V at SDN Keleyan 2. This research adopted a qualitative approach with a descriptive design. The participants consisted of one Grade V teacher and two slow learner students who had been identified as experiencing difficulties in reading, comprehending learning materials, and performing arithmetic calculations. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the teacher implemented several learning strategies, including repeated explanations using simple language, peer tutoring, the use of engaging and interactive learning media, and intensive individualized guidance. These strategies helped slow learner students improve their understanding of learning materials, participation in classroom activities, and overall engagement in the learning process. The study concludes that adapting learning strategies to the characteristics of slow learner students contributes positively to their learning participation and academic development in elementary school settings. ABSTRAK Penelitian ini dilatarbelakangi oleh keberadaan siswa slow learner di sekolah dasar yang mengalami kesulitan dalam mencapai kompetensi pembelajaran, terutama pada aspek literasi dan numerasi. Kondisi tersebut menuntut penerapan strategi pembelajaran yang sesuai dengan karakteristik dan kebutuhan siswa agar proses belajar dapat berlangsung secara optimal. Penelitian ini bertujuan untuk mendeskripsikan strategi pembelajaran yang diterapkan guru kelas dalam menangani siswa slow learner di kelas V SDN Keleyan 2. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif. Partisipan penelitian terdiri atas satu guru kelas V dan dua siswa slow learner yang telah diidentifikasi mengalami hambatan belajar pada kemampuan membaca, memahami materi, dan berhitung. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan studi dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi pembelajaran yang diterapkan guru meliputi pemberian penjelasan secara berulang dengan bahasa sederhana, penggunaan tutor sebaya, pemanfaatan media pembelajaran yang menarik dan interaktif, serta pemberian bimbingan individual secara intensif. Strategi tersebut membantu siswa slow learner meningkatkan pemahaman materi, kemampuan mengikuti kegiatan pembelajaran, dan partisipasi dalam proses belajar di kelas. Temuan ini menunjukkan bahwa penyesuaian strategi pembelajaran berdasarkan karakteristik siswa slow learner berkontribusi positif terhadap keterlibatan dan perkembangan kemampuan belajar mereka di sekolah dasar.